Critical Discourse On The Problem Of Foreign Workers In Indonesia - Adrian Akbar Pangestu; Agna Hilyah; Caesar Ahmad Maulud; Rahyuniati Setiawan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Garut, 2022)
This research was conducted to analyze the content of YouTube Channel Indonesia relating to the deliberations of the foreign labor (TKA). This analysis involves several people who discuss about issues of foreign labor. With regards to this method used is descriptive content analysis approach. This research takes the 15 videos that made the samples as the basis for the analysis of this content. The videos gained found will be in the transcript for analysis related to the phenomenon of foreign labor in Indonesia. The result of this analysis the existence of notable pros and cons against this issue.